Choroidal Characteristics of Acute and Chronic Central Serous Chorioretinopathy Using Enhanced Depth Imaging Optical Coherence Tomography. Issue 4 (26th June 2017) - Ruiz-Medrano, Jorge; Pellegrini, Marco; Cereda, Matteo G.; Cigada, Mario; Staurenghi, Giovanni
Purpose: Central serous chorioretinopathy (CSC) is an idiopathic disorder characterized by serous detachments of the neurosensory retina and/or the retinal pigment epithelium affecting the macular area in the majority of cases. The objective of this study was to describe choroidal findings in patients with acute and chronic CSC based on enhanced depth imaging optical coherence tomography analysis. Methods: This is a cross-sectional, noninterventional study performed at Luigi Sacco University Hospital of Milan. Inclusion criteria were the presence of diagnosed (acute or chronic) CSC and being 18 years or older. Patients were evaluated with Spectralis spectral-domain optical coherence tomography enhanced depth imaging by 2 operators. The main features analyzed were intrachoroidal hyperreflective spots and hyperreflective choroidal vessel walls, as actual measurements of wall thickness could not be performed. Results: Patients with chronic CSC had hyperreflective spots in 83.3% of the cases and hyperreflective choroidal vessel walls in 75%, whereas patients with acute course had the same alterations in 33% and 6.7% of cases, respectively. Conclusions: These findings, if proven, may be indicative of chronic forms, thus guiding more accurate treatments and guiding clinicians through more accurate prognosis.